On the ionic and electrostatic nature of the activation of linear cloud anomalies over seismically active zones - T. A. Belyi; Yu. A. Zelenin (Геофизический журнал, 2012)
One-dimensional model of medium self-coordinated electrostatic field (SF) of lower atmosphere (0-30 km) has been obtained. The model has been presented by Poisson equation for self-coordinated field of electrons within dense gas. Exact solution has been found in approximation of constant coefficients corresponding to integrability of classical Morse oscillator. The solution is parametrized by the values of field energy in the unit of volume. Basic functions of linear approximation, in contrast to homogenous approximation of Debye - Huckel, are Eyre functions (Ai, Bi) which show oscillation hyperpolarizing ability of electrons distribution in the gravity field. Within the limits of this model injection-polarization mechanism has been proposed of stabilization of linear cloudy anomalies (LCA) by the waves of charge density in heterogeneous (overabundant) electronic-ionic subsystem of the atmosphere in vertical stratified field. Calculations demonstrated that disturbance of surface electrostatic field from seismically active faults or edges of earthquakes sources is enough for polarization of charged subsystem of water steam of LCA.